Siyasah Dusturiyyah sebagai Sistem Perpolitikan dalam Al-Qur’an - Salman Abdul Muthalib; Muhammad Faizur Ridha bin Mohd Pauzi (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2019)
Siyasah dusturiyyah so far has not been revealed in detail. In the world history stage, it can be seen that the good or bad of a country depends on the system of government. The Qur'an has clearly stated the necessity of government. Allah SWT ordered the Messenger of Allah to get used to and train himself in government affairs. Thus, to find the ideal of Islam in the process of administering the government, the title of the thesis on